Demographic and Intellectual Bonus: Science Development Innovation Using Current Modeling - Najib Siregar, Nahrun; Milfa Laensadi, Azkya; Nurhasanah, Andi; Mardiana; Nuraida (International Journal of Education, Language, and Social Science, 2023)
The demographic bonus is the window of opportunity enjoyed by a country as a result of the large proportion of the productive population. Currently, Indonesia is experiencing a demographic bonus, and this article aims to explain the demographic and intellectual bonus as an early development of the productive age, as well as its role in fostering innovation in science through contemporary modeling. Using a descriptive analysis approach, this research draws from relevant sources such as books, articles, and studies related to the topic. The findings suggest that the demographic bonus in the productive age can be beneficial if the education system produces graduates who are productive, forward-thinking, skilled, qualified, and capable of recognizing opportunities. Conversely, it could be detrimental if the quality of human resources is low-skilled and unable to capitalize on existing opportunities. The demographic bonus that occurred was also the window of opportunity with the dependency ratio reaching its lowest point of 44 of 100 which only happened once in the history of a population. Meanwhile in the field the development of science with contemporary modeling is the Science Technology Society . Science learning with the Science Technology Society approach means using technology as a link between science and society. That means that society must be more active and carry out scientific designs on all aspects of life including its application in the field of education.